Development of Stabilized Organic Cathodes via Grafting Redox-active Molecules to Carbon in Aqueous Zinc-ion Batteries for Energy Storage Systems - Baker, Thomas (My University, 2024)
To combat climate change, governments have pledged to become more dependent on renewable electricity production. However, the intermittency of renewable power generation requires modern grid-scale energy storage systems, which are currently being explored with lithium-ion batteries (LIBs). However, this technology faces significant safety, social, and financial concerns. As an alternative chemistry, aqueous zinc-ion batteries (ZIBs) show much promise for grid-scale energy storage with their safe, inexpensive design. Major bottlenecks of ZIB performance include their limited practical specific capacity, and low capacity retention. Organic cathodes, specifically the use of redox-active quinone molecules, are an upcoming contender for customizable and simple ZIB cathode design that can be optimized for good performance. However, these cathodes are often plagued by capacity fade caused by quinone dissolution and inactivation. Grafting these quinone molecules to the supporting conductive carbon substrate via covalent bonding had been previously explored in LIB and supercapacitor electrode design as an effective way to mitigate capacity fade. In this work, the development of aqueous ZIB cathodes with 9,10-phenanthrenequinone (PQ) molecules grafted to carbon black substrates was done via a facile in-situ generated diazonium salt reaction synthesis technique. Electrochemical and material analysis confirmed the presence of covalent grafting. This grafting modification was compared to the standard cathode design of adsorbing the quinones on carbon substrates like Ketjenblack (KB) and Vulcan Black (VB). Battery cycling tests were performed and the grafted PQ-KB cells achieved a discharge capacity of 99 mAh g-1 after 1000 charge-discharge cycles with accelerated testing at a charge/discharge rate of 200 mA g-1 and 10 mA g-1. These cells maintained 67% of their initial capacity compared to the 55% for the adsorbed PQ on KB cells. This approach highlights the promise of grafting organic material as a technique to support organic cathodes for next-generation ZIB design.
Stabilized Organic Cathodes for Zinc-ion Batteries
Keywords: Zinc-ion Battery; Quinone; Grafting; Grid-Scale Energy Storage; Electrochemistry; Organic Cathode